New uracil analog U-332 is an inhibitor of NF-κB in 5-fluorouracil-resistant human leukemia HL-60 cell line - Angelika Długosz-Pokorska; Marlena Pięta; Jacek Kędzia; Tomasz Janecki; Anna Janecka (BMC, 2020)
Abstract Background 5-Fluorouracil (5-FU) is an antimetabolite that interferes with DNA synthesis and has been widely used as a chemotherapeutic drug in various types of cancers. However, the development of drug resistance greatly limits its application. Overexpression of ATP-binding cassette (ABC) transporters in many types of cancer is responsible for the reduction of the cellular uptake of various anticancer drugs causing multidrug resistance (MDR), the major obstacle in cancer chemotherapy. Recently, we have obtained a novel synthetic 5-FU analog, U-332 [(R)-3-(4-bromophenyl)-1-ethyl-5-methylidene-6-phenyldihydrouracil], combining a uracil skeleton with an exo-cyclic methylidene group. U-332 was highly cytotoxic for HL-60 cells and showed similar cytotoxicity in the 5-FU resistant subclone (HL-60/5FU), in which this analog almost completely abolished expression of the ATP-binding cassette (ABC) transporter, multidrug resistance associate protein 1 (ABCC1). The expression of ABC transporters is usually correlated with NF-κB activation. The aim of this study was to determine the level of NF-κB subunits in the resistant HL-60/5-FU cells and to evaluate the potential of U-332 to inhibit activation of NF-κB family members in this cell line. Methods Anti-proliferative activity of compound U-332 was assessed by the MTT assay. In order to disclose the mechanism of U-332 cytotoxicity, quantitative real-time PCR analysis of the NF-κB family genes, c-Rel, RelA, RelB, NF-κB1, and NF-κB2, was investigated. The ability of U-332 to reduce the activity of NF-κB members was studied by ELISA test. Results In this report it was demonstrated, using RT-PCR and ELISA assay, that members of the NF-κB family c-Rel, RelA, RelB, NF-κB1, and NF-κB2 were all overexpressed in the 5-FU-resistant HL-60/5FU cells and that U-332 potently reduced the activity of c-Rel, RelA and NF-κB1 subunits in this cell line. Conclusions This finding indicates that c-Rel, RelA and NF-κB1 subunits are responsible for the resistance of HL-60/5FU cells to 5-FU and that U-332 is able to reverse this resistance. U-332 can be viewed as an important lead compound in the search for novel drug candidates that would not cause multidrug resistance in cancer cells.